2020
DOI: 10.3390/ani10071228
|View full text |Cite
|
Sign up to set email alerts
|

Nociceptive Threshold of Calves and Goat Kids Undergoing Injection of Clove Oil or Isoeugenol for Disbudding

Abstract: In this preliminary study, we compared changes in mechanical nociceptive thresholds (MNT) of calves and goat kids injected with clove oil or isoeugenol under the horn bud as a potential, more welfare-friendly alternative to hot-iron disbudding. Twenty male calves and goat kids were randomly allocated to clove oil (n = 10 per species) or isoeugenol (n = 10 per species) injection under the horn buds. MNT was measured via a pressure algometer in calves and kids at several locations around the horn buds at several… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 46 publications
3
13
0
Order By: Relevance
“…If local reactions to the treatment occurred or in case of sickness, appropriate veterinary treatment was applied immediately as described in detail in the results. Swellings of the upper eyelids and suppurations after injection of clove oil (see results) occurred at a higher rate than would have been expected from previous studies [ 24 , 25 ]. Thus, we changed the bottle of clove oil after the treatments of the first three animals, as clove oil is a natural product without defined composition and we suspected that the composition of that specific batch might have caused these adverse effects.…”
Section: Methodssupporting
confidence: 50%
See 2 more Smart Citations
“…If local reactions to the treatment occurred or in case of sickness, appropriate veterinary treatment was applied immediately as described in detail in the results. Swellings of the upper eyelids and suppurations after injection of clove oil (see results) occurred at a higher rate than would have been expected from previous studies [ 24 , 25 ]. Thus, we changed the bottle of clove oil after the treatments of the first three animals, as clove oil is a natural product without defined composition and we suspected that the composition of that specific batch might have caused these adverse effects.…”
Section: Methodssupporting
confidence: 50%
“…The increased MNT 15 min after the treatment in CLOV as compared to CON might have been caused by their anesthetic properties [fish: 23, rats: 36]. This effect occurred also in a previous study on calves and goat kids [ 24 ]. For ISO, we found an anesthetic effect only with the PA (although not significant after Bonferroni correction) but not with the vFF; this might be due to the different locations used for the assessment; they may differ in general sensitivity, or the liquids might not have dispersed evenly [ 10 , 24 ].…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…However, the authors noted that clove oil and eugenol have anesthetic properties, and subject kids did not appear distressed based on casual observations. Conversely, Frahm et al [23] reported mechanical nociceptive thresholds increased in kids and calves within 24 h of clove oil or isoeugenol injection. Hempstead et al [3,12] observed that the acute physiologic and behavioral indicators of pain associated with clove oil disbudding were similar to cautery disbudding, though time to healing was reduced; more concerning, they were not able to fully replicate the efficacy findings of the Molaei et al study [21].…”
Section: Introductionmentioning
confidence: 95%
“…Disbudding is an animal husbandry procedure conducted on-farm as part of routine management in cattle production enterprises [ 1 ]. Removal of the horn bud and horn-budding cells is considered to cause significant pain, based on a variety of outcome measures [ 2 , 3 , 4 , 5 , 6 ]. The use of topical anaesthesia, applied to the disbudding wound immediately post-procedure, is emerging as a simple and practical method to address post-operative pain.…”
Section: Introductionmentioning
confidence: 99%